2022
DOI: 10.1111/jerd.12885
|View full text |Cite
|
Sign up to set email alerts
|

Sonic application of one‐step self‐etch adhesive in composite restorations of non‐carious cervical lesions: A double‐blind randomized clinical trial

Abstract: Objectives To evaluate the influence of the sonic device on the clinical performance of one‐step self‐etch adhesive systems in non‐carious cervical lesions (NCCLs) after 18 months. Materials and methods Forty patients participated in this study. Eighty restorations were assigned to two groups (n = 40): Sonic application and Manual application. After the adhesive application (iBond Self‐Etch, Kulzer, Hanau, Germany), NCCLs were restored using composite resin (Charisma, Kulzer, Hanau, Germany). The restorations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Regarding the evaluation criteria, some studies have considered FDI to be more sensitive to small variations in clinical outcomes than USPHS [ 58 , 59 ]. In contrast, other studies have observed no difference, and stated that both criteria worked equally well.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the evaluation criteria, some studies have considered FDI to be more sensitive to small variations in clinical outcomes than USPHS [ 58 , 59 ]. In contrast, other studies have observed no difference, and stated that both criteria worked equally well.…”
Section: Discussionmentioning
confidence: 99%
“…This was endorsed by some RCTs (Zander-Grande et al 2014;Hass et al 2022). The vigorous manual application (Zander-Grande et al 2014) and sonic application (Hass et al 2022) improved an important clinical outcome: the retention rates of noncarious cervical restorations. Thus, for this protocol, one of the pillars of EBP, the use of the best available evidence, was contemplated.…”
Section: When Laboratory and Clinical Trials Match: What Should We Lo...mentioning
confidence: 98%